2008
DOI: 10.1016/j.anl.2007.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Post-operative pharyngocutaneous fistula after laryngectomy

Abstract: Objectives: Although organ-preserving radiotherapy or chemoradiotherapy have offered good locoregional control, many patients still experience recurrent disease requiring salvage laryngectomy. The pharyngocutaneous fistulae (PCF) is a common and troublesome complication in the early postoperative period after laryngectomy.Here we evaluated the cause of PCF after laryngectomy, with special emphasis on radiotherapy and/or chemotherapy. Study Design: Retrospective chart review. Methods:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 21 publications
(28 reference statements)
2
49
3
Order By: Relevance
“…These include age [22, 23], positive histological margins [2325], suture material [2, 12, 26], primary voice puncture [2729], oral feeding [30], type of pharyngeal closure [19, 26, 31, 32]. The antibiotics given and their duration depending on the centre [33] but there is no clear evidence for any specific antibiotic regime [34] although clindamycin has been shown to increase complication rates [35].…”
Section: Discussionmentioning
confidence: 99%
“…These include age [22, 23], positive histological margins [2325], suture material [2, 12, 26], primary voice puncture [2729], oral feeding [30], type of pharyngeal closure [19, 26, 31, 32]. The antibiotics given and their duration depending on the centre [33] but there is no clear evidence for any specific antibiotic regime [34] although clindamycin has been shown to increase complication rates [35].…”
Section: Discussionmentioning
confidence: 99%
“…This complication leads to increased morbidity, prolonged hospitalization, and greater hospital care expenditure 9,10 . The same happens to patients with early recurring laryngeal tumors after radiotherapy alone 5,6 . In an attempt to prevent or reduce the incidence of salivary fistulas, some authors have advocated the routine use of non-irradiated tissue to reinforce and close the larynx.…”
Section: Introductionmentioning
confidence: 85%
“…On a meta-analysis, Paydarfar & Birkmeyer 15 showed that preoperative radiotherapy increases the risk of pharyngocutaneous fistulas (RR, 2.28; p < 0.001), confirming the findings of other papers, in which fistula incidence rates ere higher in previously irradiated patients when compared to non-irradiated subjects as described by Ganly et al 12 (32% versus 12%, p = 0.012 respectively). The effect of radiotherapy translates into injuries to tissue microvasculature, resulting in myointimal fibrosis, endarteritis, and worsening of atherosclerosis, leading to a hypovascular, hypocellular, and hypoxic environment, reducing healing capacity, increasing the risk for fistula formation, its severity, and duration 5,15,17 . The use of non-irradiated flaps has been recommended to reduce the incidence rates and the morbidities associated with salivary fistulas in salvage laryngectomy patients, even when thee is enough mucosa for a primary closure procedure 3,7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clark et al [29] showed that irradiation increased the incidence of postoperative pharyngo-cutaneous fistula from 24% to 38% while Wakisaka [30] et al noted that although the frequency of pharyngocutaneous fistula after RT or CRT was not high, fistula closure tended to be delayed. In their series, Taki et al [5] experienced severe postoperative complications including pharyngocutaneous fistulas in 25% of patients who underwent laryngopharyngectomy.…”
Section: Discussionmentioning
confidence: 99%